Comparison of Lower Stratosphere Wind Observations From the USTC's Rayleigh Doppler Lidar and the ESA's Satellite Mission Aeolus. Issue 8 (15th August 2022) - Chen, Chong; Xue, Xianghui; Sun, Dongsong; Zhao, Ruocan; Han, Yuli; Chen, Tingdi; Liu, Hengjia; Zhao, Yiming
Abstract: Since the first spaceborne Doppler wind lidar, Aeolus, was launched, global wind field observations from space have been possible. Several ground‐ and air‐based validations followed, although most of these comparisons remained below 10 km in the troposphere, with rare validation work for the stratosphere. The Rayleigh Doppler lidar developed by the University of Science and Technology of China (USTC) was deployed in Xinjiang, China, in 2017. It can observe wind speed and temperature in the stratosphere and mesosphere. By setting two geographical ranges centered on the USTC lidar, the Aeolus Rayleigh winds within these ranges can be compared with ground‐based lidar wind data. Furthermore, after eliminating the effect of particulate backscatter on the USTC lidar, the lower limit of the detection range was extended to 10 km to obtain more samples. The mean biases between the Aeolus winds and the USTC lidar winds were 1.05 ± 5.98 (−0.35 ± 4.78) m/s, 1.80 ± 6.30 (−1.88 ± 4.97) m/s, and 0.17 ± 5.45 (0.51 ± 4.44) m/s for all data, ascending orbits, and descending orbits, respectively, in a large (small) geographical range. The geographical distance between the USTC lidar and the Aeolus observation swaths has a significant effect on the wind bias, the farther the distance between Aeolus observation swaths and the USTC lidar, the greater the bias. Whereas, the wind biases have no significant dependency on the time difference of the USTC lidar observation to Aeolus overflight time. Overall, the Aeolus winds are consistent with the USTC lidar winds in the stratosphere. Key Points: Comparison between the University of Science and Technology of China (USTC) Rayleigh Doppler lidar winds and the Aeolus Level‐2B Rayleigh winds in the stratosphere in 2019 Ground‐based measurements are utilized for the validation of stratospheric wind data from Aeolus Overall, the Aeolus winds are consistent with the USTC lidar winds with acceptable biases